Nesting sites of the Cape Sparrow "Passer Melanurus" in Maloti/Drakensber, Southern Africa - Kopij, Grzegorz (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In Maloti/Drakensberg region, southern Africa, Cape Sparrow locates nests (N=108) mainly in trees (38.9%), shrubs (27.8%) and man-made structures (29.6%). Most occupied trees were exotic (31.6%), while all (27.8%) occupied shrubs were indigenous. A few nests (3.8%) were found in disused weavers` nests. Nesting sites ranged in height from 1.5 m to 10 m above the ground; on average ? 4.2 m (N=52).
Keywords: nest sites; weavers; Lesotho